1998
DOI: 10.1002/jlb.64.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil degranulation and phospholipase D activation are enhanced if the Na+/H+ antiport is blocked

Abstract: To investigate the role of the pH transient in controlling degranulation, the Na ؉ /H ؉ antiport was inhibited either with 100 M dimethylamiloride (DMA) or by substituting N-methyl-glucamine for extracellular sodium. Blocking the antiport with DMA led to hyperacidified PMN, which exhibited an increase in degranulation, but did not affect generation of superoxide. DMA did not alter the ability of neutrophils to phagocytose and oxidize dichlorodihydrofluoresceinated HIC, suggesting the increase in degranulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…There are myriad potential pH-and CO 2 -dependent molecular targets that are critical for the maintenance of cell structural integrity in the face of deforming stress (8,20). In functional terms, they involve complex systems mediating cytoskeletal remodeling as well as lipid and vesicular trafficking to and from the plasma membrane (27).…”
Section: Discussionmentioning
confidence: 99%
“…There are myriad potential pH-and CO 2 -dependent molecular targets that are critical for the maintenance of cell structural integrity in the face of deforming stress (8,20). In functional terms, they involve complex systems mediating cytoskeletal remodeling as well as lipid and vesicular trafficking to and from the plasma membrane (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a widely expressed class of vesicles, called enlargosomes, has been identified in secretory and nonsecretory mammalian cells and has been implicated in membrane repair (51). Even this extremely sketchy account of plasma membrane resealing identifies a host of potentially pH-sensitive target molecules: vesicle docking and fusion proteins, molecular motors, second messengers of membrane-adhesive interactions such as phosphatidylinositol 4,5-bisphosphate and the proteins that control its activity, protein kinase C-dependent Golgi export, and cellular Ca 2ϩ homeostasis itself (52,53). Although our statistical confidence in the effects of hypercapnia on cell repair is stronger than that pertaining to hypocapnia, all our observations, be they in whole lungs or cell culture models, suggest that positive as well as negative deviations from the eucapnic state alter cellular repair responses.…”
Section: Molecular Mechanisms Of Plasma Membrane Repairmentioning
confidence: 99%
“…The initial rapid cytoplasmic signals initiated by fPR1 have been studied extensively; they are followed within less than 1 min by a redistribution such that a final [Ca 2ϩ ] i up to 100 nM above the resting [Ca 2ϩ ] i ([Ca 2ϩ ] i 0 ) of naïve PMN as well as a pH i 0.2 to 0.3 units higher than its resting pH i (pH 0 ) of 7.05 to 7.07 are attained (2, 15, 37). These changes, in turn, cause the PMN, after cytoskeletal rearrangement (15,33,37) and expression of adhesion proteins on their surface, to move (chemotax) up the chemoattractant gradient to its source via multiple contacts between a given PMN and higher fMLP concentrations (32), a motion that has been captured in real time (23).Many investigations have shown that at or below 100 nM, liganding with fMLP does not induce the activation of the bactericidal functions of human PMN (e.g., oxidative burst and lytic enzyme and inhibitory protein release) unless the PMN have been primed (3,6,13,15,39,48,50). When the PMN reach the maximal chemoattractant concentration and hence the entity from which it originated, a different set of receptors, such as Fc␥R, C3R, CD14, and Toll-like receptor (specific receptors for the Fc ends of immunoglobulin G, complement components, lipopolysaccharides, and Toll-like ligands, respectively), which mediates phagocytosis and degranulation, is liganded by the entity itself or its coating opsonins, and the bactericidal functions of the PMN are initiated (30).…”
mentioning
confidence: 99%
“…Naïve PMN have been shown to possess two classes of fMLP receptors (fPR1 and fPR2, of high and low affinity, respectively) (25,(40)(41)(42)(43), which, when liganded with up to 100 nM peptide, mediate the activation of signals, including a rapid transient rise in cytoplasmic Ca 2ϩ ([Ca 2ϩ ] i ), due largely to release from intracellular stores, and a simultaneous drop in cytoplasmic pH (pH i ) (14,19,26,27,37); when the fMLP concentrations are above 1 M, the loweraffinity fMLP receptor also initiates some release of bactericidal entities (7,25,42,43,49). The initial rapid cytoplasmic signals initiated by fPR1 have been studied extensively; they are followed within less than 1 min by a redistribution such that a final [Ca 2ϩ ] i up to 100 nM above the resting [Ca 2ϩ ] i ([Ca 2ϩ ] i 0 ) of naïve PMN as well as a pH i 0.2 to 0.3 units higher than its resting pH i (pH 0 ) of 7.05 to 7.07 are attained (2,15,37). These changes, in turn, cause the PMN, after cytoskeletal rearrangement (15,33,37) and expression of adhesion proteins on their surface, to move (chemotax) up the chemoattractant gradient to its source via multiple contacts between a given PMN and higher fMLP concentrations (32), a motion that has been captured in real time (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation